Islam Dan Penutup Aurat: Kajian Tafsir Maudhu'i Tentang Cadar, Jilbab, Dan Burqa - Agung Wijaya; Ahmad Affandi Khaerul Fatihin; Subhan, Ahmad Subhan; Asep Abdul Muhyi (Medpro, 2023)
This study explores the Islamic concept of covering aurat, focusing on the practices of wearing the veil (cadar), jilbab, and burqa through the lens of Maudhu'i tafsir (thematic interpretation of the Quran). The research examines the historical, cultural, and religious contexts of these garments, addressing their significance within Islamic teachings and their evolution over time. Utilizing a qualitative, descriptive approach, the study delves into secondary sources, including scholarly articles, books, and Quranic interpretations, to provide a comprehensive analysis of these practices. The findings highlight the diversity of opinions among Islamic scholars regarding the obligation and interpretation of these garments, reflecting varying cultural and societal influences. The study also discusses the social and cultural implications of wearing these garments in contemporary society, including the challenges and controversies they pose. This research contributes to a deeper understanding of the role of these garments in the lives of Muslim women and offers insights into the broader discourse on religious dress codes within Islam.